2012
DOI: 10.1063/1.4728111
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of the constituent azimuthal and radial mode indices for light fields possessing orbital angular momentum

Abstract: A wide array of diffractive structures such as arrays of pinholes, triangular apertures, slits, and holograms have all recently been used to measure the azimuthal index of individual Laguerre-Gaussian beams. Here, we demonstrate a powerful approach to simultaneously measure both the radial and azimuthal indices of pure Laguerre-Gaussian light fields using the method of principal component analysis. We find that the shape of the diffracting element used to measure the mode indices is in fact of little importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…Other methods for measuring the topological charge of an optical vortex have included the diffraction intensity pattern after an axicon [18] or an annular triangle aperture [19]. Very recent studies have shown the use of multivariate statistical analysis for the diffraction pattern from any arbitrary aperture and shown that by training the system one may deduce the index m of the vortex from the diffraction pattern of any aperture [20]. While some of above methods may deal with vortices generated with temporally incoherent light, it is noteworthy that all of these methods have assumed that the optical field is fully spatially coherent.…”
mentioning
confidence: 99%
“…Other methods for measuring the topological charge of an optical vortex have included the diffraction intensity pattern after an axicon [18] or an annular triangle aperture [19]. Very recent studies have shown the use of multivariate statistical analysis for the diffraction pattern from any arbitrary aperture and shown that by training the system one may deduce the index m of the vortex from the diffraction pattern of any aperture [20]. While some of above methods may deal with vortices generated with temporally incoherent light, it is noteworthy that all of these methods have assumed that the optical field is fully spatially coherent.…”
mentioning
confidence: 99%
“…The second one is diffraction-based schemes [26][27][28][29][30][31][32][33][34] in which the diffraction pattern of the photons through an obstacle is observed. The magnitude of can be decided according to the patterns.…”
Section: Figmentioning
confidence: 99%
“…This property can be used, for example, to simultaneously measure the azimuthal and radial modes of Laguerre-Gaussian beams [5,6]. It is interesting to consider the possibility of using this very same approach in random media to measure other key properties of the light field such as polarization state or wavelength.…”
mentioning
confidence: 99%
“…This algorithm is similar to the one that we used for the detection of the azimuthal and radial mode indices of higher-order Laguerre Gaussian beams [5]. The procedure consists of two parts.…”
mentioning
confidence: 99%
See 1 more Smart Citation